The Impact of Anxiety and Self-Motivation Based on Mathematical Literacy - Widyaningrum, Azzahra; Faradillah, Ayu (Pendidikan Matematika UNIMOR, 2025)
Mathematical literacy skills play an important role in students' learning success as it helps them understand and apply mathematical concepts in everyday life, while anxiety experienced during the learning process can hinder this ability, and strong self-motivation is needed to drive and sustain actions focused on achieving specific goals. Although extensive research on the impact of math anxiety and motivation has been conducted, few studies have explored the simultaneous interaction of these variables in influencing students' mathematical literacy. This study aims to examine how math anxiety and self-motivation interact and influence students' mathematical literacy skills. Using a qualitative phenomenological approach, data were from 66 tenth grade students at a public high school in Jakarta. The instruments used included a validated mathematics literacy test, anxiety and motivation questionnaires, and interview guidelines. The validity and reliability of the questionnaire was assessed using Winsteps 3.73 software, and three representative students were selected based on the Wright Map results for testing and in-depth interviews.The research findings revealed that students with low anxiety and high self-motivation demonstrated the highest mathematical literacy performance, while students with high anxiety and low self-motivation demonstrated limited problem-solving ability and self-confidence. Moderate levels of both factors resulted in average performance, with little doubt but fundamental logical development. This research implies that educational strategies should address the emotional and self-motivational aspects of learning.